Formative use of Wordwall in supporting vocabulary and reading comprehension achievement among elementary students - Isnaini, Risdatul; Masagus Firdaus (Jurnal CULTURE (Culture, Language, and Literature Review), 2025)
This study examines the formative use of Wordwall as a gamified digital learning tool to enhance vocabulary mastery and reading comprehension among elementary EFL learners at MIN 1 Ogan Ilir. Despite the increasing integration of digital platforms in early language education, research on how gamified tools function as formative assessment mechanisms remains limited, particularly in Indonesian primary school contexts. Employing a qualitative, library-based research design, this study synthesizes empirical findings from recent peer-reviewed publications to analyze Wordwall’s pedagogical affordances, challenges, and learning outcomes. The review reveals that Wordwall supports vocabulary acquisition through interactive tasks that promote repetition, contextualization, and immediate corrective feedback. In reading comprehension, features such as Group Sort, Matching Pairs, and Quiz facilitate learners’ ability to identify main ideas, sequence events, and make inferences. Gamification elements; including leaderboards, timers, and reward systems, further increase learners’ engagement and intrinsic motivation, contributing to a more active and student-centered learning environment. However, the findings also highlight practical challenges such as unequal device access, unstable connectivity, and limited teacher digital literacy, which require adaptive instructional strategies for equitable implementation. Overall, this study underscores the value of integrating gamified formative tools like Wordwall to strengthen young learners’ vocabulary and reading skills. It recommends that schools provide stronger technological support and professional development to maximize the educational impact of digital formative assessment in primary EFL classrooms.